Actitud del paciente con VIH/SIDA y calidad de cuidado de enfermería - Rodríguez Villegas de Zuta, Keli Maribel (2019)
The present research work is descriptive, correlational and cross-sectional, aimed at: Determining the relationship between the Attitude of the patient with HIV / AIDS and the quality of nursing care treated in the Emergency Service of the High Complexity Hospital Virgin of the Door. The sample consisted of 80 patients, to whom the following instruments were applied: Questionnaire on the attitude of the patient with HIV / AIDS and Survey on quality of nursing care. Pearson's statistical test was used to relate the variables under study to the following results: 69% of patients have a negative attitude and 31% have a positive attitude. Regarding the quality of nursing care, 89% reported receiving a quality of regular nursing care, 11% a poor quality of nursing care. Concluding that there is a low positive correlation between both variables.(p= 0,005)